Immigration and the Political Economy of Public Education: Recent Perspectives - Francesc Ortega; Ryuichi Tanaka (Institute for the Study of Labor (IZA), 2015)
This paper reviews the recent literature on the effects of immigration on the public education of the host country, emphasizing the political economy implications. In particular, we are interested on what happens to enrollment in public schools and the quality of education in these schools. Our review of the literature, which includes both quantitative and empirical studies, suggests the following conclusions. First, immigration has triggered native flight toward private schools in a wide variety of contexts. Some studies also find that the households that switch to private schools tend to be those with higher socio-economic status. Secondly, because of these changes in school choices, one consequence of large-scale immigration is that it appears to undermine the political support for public education, resulting in a deterioration in the funding and quality of public schools that seems to affect negatively the educational outcomes of disadvantaged native students. We offer some suggestions for policies that might help mitigate the negative consequences of immigration outlined above so that host countries can maximize the overall economic benefits of immigration.
Keywords: D7; F22; H52; H75; J61; I22; I24; 330; education; public school; immigration; naturalization